Trust among the avatars: A virtual world experiment, with and without textual and visual cues - Stephen Atlas; Louis Putterman (Brown University, Department of Economics, 2010)
We invited residents of a virtual world who vary in real-world age and occupation to play a trust game with stakes comparable to in world wages. In different treatments, the lab wall was adorned with an emotively suggestive photograph, a suggestive text was added to the instructions, or both a photo and text were added. We find high levels of trust and reciprocity that appear still higher for non-student and older subjects. Variation of results by treatment suggests that both photographic and textual cues influenced the level of trust but not that of trustworthiness.
Keywords: C70; C91; D03; 330; trust; experiment; internet; virtual world; priming